Type 2 diabetes mellitus’ impact on heart failure patients’ exercise tolerance: a focus on maximal fat oxidation during exercise - Zhu, Huiying; Pan, Jianchao; Wen, Jianxuan; Dang, Xiaojing; Chen, Xiankun; Fan, Yunxiang; Lu, Weihui; Jiang, Wei (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo explore the impact of type 2 diabetes mellitus (T2DM) on exercise tolerance and fat oxidation capacity in patients with heart failure (HF).MethodsWe retrospectively analyzed 108 Chinese patients with HF who were divided into a diabetic group (T2DM group, n = 47) and a non-diabetic group (non-T2DM group, n = 61). All subjects completed cardiopulmonary exercise testing (CPX). We determined their fat oxidation (FATox) by indirect calorimetry.ResultsIn the HF patients, the peak oxygen uptake (VO2) value was 14.76 ± 3.27 ml/kg/min in the T2DM group and 17.76 ± 4.64 ml/kg/min in the non-T2DM group. After adjusting for age, sex, body mass index (BMI), log N-terminal pro-B type natriuretic peptide (log NT-proBNP), left ventricular ejection fraction (LVEF), hemoglobin, renal function, coronary heart disease and hypertension, the peak VO2 was lower in the T2DM group compared to the non-T2DM group with a mean difference (MD) of −2.0 ml/kg/min [95% confidence interval (CI), −3.18 to −0.82, P < 0.01]. The VO2 at anaerobic threshold (AT VO2) was also lower in the T2DM group than in the non-T2DM group, with a MD of −1.11 ml/kg/min (95% CI −2.04 to −0.18, P < 0.05). Regarding the fat oxidation capacity during CPX, the T2DM group's maximal fat oxidation (MFO) was lower than that of the non-T2DM group (0.143 ± 0.055 vs. 0.169 ± 0.061 g/min, P < 0.05). In addition, the T2DM group had lower FATox at exercise intensity levels of 40% (P < 0.05) and 50% (P < 0.05) of peak VO2, compared to the non-T2DM group.ConclusionsT2DM is associated with a decrease in exercise tolerance and fat oxidation capacity in patients with heart failure. Thus, it could be useful to develop exercises of appropriate intensity to optimize physical and metabolic health.